Efficiency Analysis of EU Member States in the Context of Population Aging - Soukupova, Nikola; Kocourkova, Marketa; Klicnarova, Jana (Ekonomický časopis/Journal of Economics, 2025)
The population aging might threaten the economic development and efficiency of EU Member States. Based on the demographic projections, the EU’s old-age dependency ratio (as proxies of population aging) will be almost double – from 31% in 2019 to 57% in 2100. This study focuses on the efficiency analysis of European Union Member States in the context of population aging. Utilizing Data Envelopment Analysis (DEA) and the Malmquist Productivity Index, we evaluated how demographic changes affect the economic efficiency of various EU countries. Our findings reveal that some states, such as the Czech Republic, Germany, and Luxembourg, demonstrate high-efficiency levels when considering demographic factors. The results suggest that technological advancement and innovation are crucial in addressing the challenges associated with population aging.